The Existence of the Manuscript in Minangkabau Indonesia and its Field in Islamic Studies - Taufiqurrahman, Taufiqurrahman; Hidayat, Ahmad Taufik; Efrinaldi,; Sudarman,; Lukmanulhakim, (Journal of Al-Tamaddun, 2021)
The existence of manuscripts in the Minangkabau area has undergone a development that is not only in certain surau but can even be found in various places in Minangkabau. The text of the manuscript is generally related to Islamic studies, so that the direction of the scientific field of study will support scientific development in the fields of ḥadīth, shari‘a, history, Islamic education and the development of thought, philosophy (manṭīq), and Sufism. This study uses primary data derived from existing manuscripts with philology and codicology approaches. This approach uses manuscripts as research sources to be presented in a mapping which has been identified that philology, codicology, and paratext studies are the initial bases in studying aspects of the text in Minangkabau manuscripts. On this basis, Islamic studies institutions have a great opportunity to study the most important aspects of the manuscript or to use the manuscript as the main source. This is related to the study of manuscripts in the development of ḥadīth studies, development of shari‘a studies, development of historical studies, development of Islamic education and thought, philosophy (manṭīq), and Sufism.